2020
DOI: 10.1111/mec.15376
|View full text |Cite
|
Sign up to set email alerts
|

Local adaptation across a complex bioclimatic landscape in two montane bumble bee species

Abstract: Understanding evolutionary responses to variation in temperature and precipitation across species ranges is of fundamental interest given ongoing climate change. The importance of temperature and precipitation for multiple aspects of bumble bee (Bombus) biology, combined with large geographic ranges that expose populations to diverse environmental pressures, make these insects well‐suited for studying local adaptation. Here, we analyzed genome‐wide sequence data from two widespread bumble bees, Bombus vosnesen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
83
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 51 publications
(99 citation statements)
references
References 122 publications
(231 reference statements)
16
83
0
Order By: Relevance
“…The map was created in ESRI ArcMap 10.8, with state outlines and digital elevation data obtained from https ://www.diva-gis.org/Data. The B. vosnesenskii range outline was taken from the species distribution model published perviously 3,33 . (B) Mean monthly temperatures over the course of a year for queen collecting sites.…”
Section: Region Of Origin and Temperature Both Effect Expression Pattmentioning
confidence: 99%
See 1 more Smart Citation
“…The map was created in ESRI ArcMap 10.8, with state outlines and digital elevation data obtained from https ://www.diva-gis.org/Data. The B. vosnesenskii range outline was taken from the species distribution model published perviously 3,33 . (B) Mean monthly temperatures over the course of a year for queen collecting sites.…”
Section: Region Of Origin and Temperature Both Effect Expression Pattmentioning
confidence: 99%
“…1). B. vosnesenskii occurs across broad altitudinal ranges throughout its distribution, and is characterized by weak genetic differentiation (genome-wide F ST = 0.003), facilitating identification of strong local effects with little confounding influence from population structure 3,33 . We employed a common-garden style approach with laboratory colonies reared from queens collected at high and low elevations at both high and low latitudes to separate species-wide responses to thermal stress from population-specific differences that may reflect local adaptation.…”
mentioning
confidence: 99%
“…Such patterns may reflect some true rearrangements between the focal species assemblies and B. terrestris genome that have occurred over 18-20 million years of divergence but may also be the result of a small number of assembly artifacts. Our focused MAUVE analysis of the region containing a high density of putatively adaptive loci from prior studies (including a possible color-associated gene Xanthine dehydrogenase/oxidase-like; Pimsler et al 2017;Ghisbain et al 2020;Jackson et al 2020) revealed a single collinear block ( Figure 5A, B). This suggests no major rearrangements in the new genomes with respect to the B. impatiens genome previously used as a reference genome for population genomics in these species.…”
Section: Genome Comparisonsmentioning
confidence: 87%
“…We expect these new references will quickly become useful for bumble bee biologists. For example, the species included here have all recently been studied with genomic data to detect the influence of climate and landscape composition on dispersal and local adaptation (Jackson et al 2018;Jackson et al 2020;Mola et al 2020), however, such studies have largely been limited to genome-reduction methods (e.g., RAD-seq) and have required cross-species mapping to available reference genomes. These new assemblies will open the door for more extensive whole genome resequencing to uncover unique genomic variation that may be shaped by environmental conditions for each species (Fuentes-Pardo and Ruzzante 2017).…”
Section: Genome Comparisonsmentioning
confidence: 99%
See 1 more Smart Citation